The influence of coordination and supervision aspect toward effectiveness of Organization in Governmental Administration Area of Banyuasin (Research, Society and Development, 2020)
This research has a purpose to Analyze Coordination and Supervision influence toward Organizational Effectiveness in Governmental Area of Banyuasin District and intended to obtain the data from that analysis. starts from the fundamental problems of low Organizational Effectiveness of Governmental Administration Area, Regional Technical Institutions and Governmental Departments in the Regency of Banyuasin. This thought to have been came by Coordination and Supervision to Organizational Effectiveness of the Government Administrational Area, Regional Technical Institutions and Governmental Departments in the Regency of Banyuasin, not yet implemented. The approach in this study refers to the context of the theory of coordination and supervision also Organizational Effectiveness as part of the scope of Public Administration. The method of research used qualitative-quantitative and explanatory survey research with technical analysis Structural Equation Modeling (SEM), while the population of the Government Administrational Area, Regional Technical Institutions and Governmental Departments in the Regency of Banyuasin. The result of the research shows the need for the undertaking of further research regarding the need to optimize the improvement of the influence of Coordination and Supervision to Organizational Effectiveness of the Government Administrational Area, Regional Technical Institutions and Governmental Departments in the Regency of Banyuasin as seen from the perspective of Public Administration. This is shown by the existence of different variables which influence Organizational effectiveness of Coordination and Supervision to Organizational Effectiveness of the Government Administrational Area, Regional Technical Institutions and Governmental Departments in the Regency of Banyuasin.